Factors associated with violence against male commercial sex workers in highly-urbanized cities in Central Luzon - Eda, Rodmar John N. (Animo Repository, 2017)
The study sought to determine the factors affecting violence against sex workers and the level of vulnerability to HIV, AIDS and other STIs among male commercial sex workers (CSWs) in highly-urbanized cities (HUCs) in Central Luzon Region. This quantitative study used descriptive research design and utilized the survey method for its data collection. Specifically, a self-administered survey questionnaire was given to 100 male CSWs selected through purposive sampling. This study specifically sought to identify the relationship of the personal characteristics of male CSWs, their lifestyle risk practices, knowledge on violence to their level of experience of violence and the relationship of the level of experience of violence with their perceived vulnerability to HIV, AIDS and other STIs. Generally, the male CSWs were aged 24-29 and are mostly living in urban areas. Almost half of them were single and a majority were able to graduate from high school. Also, almost half of the male CSWs smoke cigarette and most of them drink alcohol. They also had a high level of knowledge on violence. The study also revealed that there was a low level of violence among male CSWs. Marital status was found to have a significant relationship with sexual and economic type of violence while educational attainment had a significant relationship with physical, emotional and economic types of violence. Lifestyle risk practices also had a significant relationship with physical violence while knowledge had a significant relationship with emotional violence. Finally, the perceived vulnerability to HIV, AIDS and other STIs also had a significant relationship with the level of experiences of violence of male CSWs. This means that various factors have effects on the experiences of violence among sex workers and, such violence also affects their perceived vulnerability to HIV, AIDS and other STIs.